Sistem Pakar Diagnosa Penyakit Pencernaan Pada Manusia Menggunakan Metode Forward Chaining - , Ramdan Alfarisi; Rengga Herdiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Cilogram sub-district is a sub-district located at the southern end of Lebak Regency. With the condition of the distance that is far from the center of the district government, it results in less even distribution of health services to the community. In the world of health, we know that there are several diseases that have long been the concern of medics and health experts, because many people suffer from them and some even result in death, one of which is a disease of the digestive system. This disease is a dangerous disease because it is directly related to the organ system in the body such as the stomach, intestines, and other organs in the digestive system. Digestive diseases are one of the focus problems in the Cilograng sub-district because many people are affected due to lack of attention to food health and nutrition-related counseling to the community. With the following problems, a new breakthrough is needed to help people get information related to digestive diseases, namely the existence of an Expert System. Expert system is one of the sub-fields of Artificial Intelligence (AI) that adopts human knowledge to computers in order to solve problems as experts usually do (Suryadi, 1994). And to facilitate inference of symptoms so as to find new facts from the symptoms consulted, this expert system uses the forwerd chaining method which starts with a search for known facts, then matches these facts with the IF part of the IF-THEN rules. If there is a fact that matches the IF part, then the rule is executed.